Synthesis of Fluorescent Sulfur Quantum Dots for Bioimaging and Biosensing - Ruan, Hong; Zhou, Li (Frontiers in Bioengineering and Biotechnology, 2022)
The rapid development of industrialization has had a serious impact on the environment, leading to an increase in disease and health care problems. The development of simple and effective biosensors to achieve specific analyte detection and bioimaging can provide useful information for disease prevention and treatment. Sulfur quantum dots (SQDs), as a new class of metal-free fluorescent nanomaterial, are being studied and applied in diagnostic fields such as bioimaging and biosensing due to their advantages of simple synthetic process, unique composition, ultra-small size, adjustable fluorescence and low toxicity. This mini review highlights the main synthetic methods to fluorescent SQDs and their recent progress in cell and tissue imaging as well as detection of biomolecules, metal ions and temperature. Finally, the future development and some critical challenges of SQDs as a fluorescent probe in the field of bioimaging and biosensing are also discussed.